The Influence of 3A (Attractions, Accessibility, and Amenities) on Tourists' Decisions to Visit Ciptaland Beach, Batam City - Setiawan, Suci Kintani Izzumi; Lubis, Arina Luthfini; Supardi, Supardi (E-Journal of Tourism, 2023)
Sekupang District in Batam City has several interesting tourist attractions, including beautiful beaches, one of which is Ciptaland Beach. The view of Singapore is very clear and the beauty of Ciptaland Beach is very amazing, but there are no tourist attractions displayed, the lack of attractions shown makes this tourist destination seem less attractive to visiting tourists. Apart from that, there are less supportive amenities such as public toilets, places to eat and parking areas. And also, accessibility in the form of inadequate road conditions, there is damage along the way to the beach location, causing a lack of comfort for tourists. This study uses a quantitative approach. The number of samples taken was 68 respondents from the total average visitors per month. The data collection techniques used were questionnaires using a Likert Scale, literature study, observation and documentation. The analysis technique used is Descriptive Statistics. Through the results of the validity and reliability tests that have been carried out, the questionnaires distributed are valid and reliable. Through the partial t influence test, as well as simultaneously, the variables Attraction (X 1 ), Accessibility (X 2 ), and Amenities (X 3 ) have a positive influence on the Visiting Decision variable (Y). The results of the hypothesis test show that the alternative hypothesis for all variables is accepted. The formulation of the results of the multiple linear regression equation is Y = 14.410 + 0.231 X 1 + 0.736 X 2 – 0.577 X 3 . Attractions, Accessibility and Amenities factors simultaneously influence the decision to visit as much as 14.8%, the remaining 85.2% is outside of the variables determined by this research.